Quality of pasta made of cassava, peach palm and golden linseed flours - SAKURAI,Yasmin Caroline Nóvoa (2020)
Abstract The possibility of industrially producing new types of pastas based on other types of flour than wheat has raised interest for enabling the use of widely available materials and providing adequate products to persons with celiac disease. A mixture design was developed with the purpose of preparing a gluten-free dry using cassava starch, peach palm meal, and golden linseed while observing the nutritional value added and its technological properties. The pasta underwent assessments of its physicochemical and rheological characteristics. The drying temperatures studied were 60, 75, and 90 °C and the influence of those temperatures on pasta quality parameters and texture properties assessed. The percentage composition of the flours met the standards mandated by the Brazilian legislation and the pasta was classified as rich in fibers. The texture parameters of the pasta were influenced by the drying process, with the best results obtained at the lowest and highest temperatures studied.